An Automated Syphilis Serology Record Search and Review Algorithm to Prioritize Investigations by Health Departments. Issue 12 (December 2021) - Karki, Saugat; Peterman, Thomas A.; Johnson, Kimberly; Hennessy, Robin R.; Matthias, James; Wilson, Craig; Mishra, Ninad; Weinstock, Hillard
Abstract : Background: Reactive syphilis serologies are investigated by health departments to determine if they represent new infection, reinfection, or treatment failure. Serologies prioritized for investigation based on nontreponemal test titer and age (using a "reactor grid") undergo manual record search and review. We developed a computerized algorithm that automates the record search and review. Methods: We developed and tested the algorithm using a Florida Department of Health data set containing serologies reported January 2016 to December 2018 and previous records linked to each individual. The algorithm was based on the syphilis case definition, which requires (except primary cases with signs and symptoms) (1) a positive treponemal test result and a newly positive nontreponemal test result or (2) a 4-fold increase in nontreponemal test titer. Two additional steps were added to avoid missing cases. New York City Department of Health and Mental Hygiene validated this algorithm. Results: The algorithm closed more investigations (49.9%) than the reactor grid (27.0%). The algorithm opened 99.4% of the individuals investigated and labeled as cases by the health department; it missed 75 cases. Many investigations opened by the algorithm were closed by the reactor grid; we could not assess how many would have been cases. In New York City, the algorithm closed 70.9% of investigations, likely because more individuals had previous test in the database (88.2%) compared with Florida (56.5%). Conclusions: The automated algorithm successfully searched and reviewed records to help identify cases of syphilis. We estimate the algorithm would have saved Florida 590 workdays for 3 years. Abstract : We designed and tested an automated record search algorithm based on the syphilis case definition that prioritized reactive serologic tests for investigation by health departments. It successfully distinguished likely cases from noncases.Supplemental digital content is available in the text.